Analysing the physics learning environment of visually impaired students in high schools. (13th June 2017) - Toenders, Frank G C; de Putter-Smits, Lesley G A; Sanders, Wendy T M; den Brok, Perry
Abstract: Although visually impaired students attend regular high school, their enrolment in advanced science classes is dramatically low. In our research we evaluated the physics learning environment of a blind high school student in a regular Dutch high school. For visually impaired students to grasp physics concepts, time and additional materials to support the learning process are key. Time for teachers to develop teaching methods for such students is scarce. Suggestions for changes to the learning environment and of materials used are given.